THE DISCREPANCY BETWEEN DECLARED VALUES AND REAL ETHICAL BEHAVIOUR OF COMPANIES (ESTONIAN CASE) - Merle Rihma; Mari Meel (European Scientific Journal, ESJ, 2013)
Many corporations present their corporate values, mission and executive principles on their website or in the public manifesto. During the recent years, describing and presenting the values of a company to the public and taking part in social reporting seems to be a growing trend in Estonia. In reality, the declared values oftentimes do not work and the actual managerial decisions are not influenced by the values or mission declared.The aim of this paper is to describe how organizations express their values and to analyse does how the behaviour of manages are cconsistent with the declared values. Through media monitoring the authors find out is there any discrepancies between declared values and real ethically responsible behaviour.The issue gained momentum after several companies, which had recently won high places in competitions responsible and sustainable business in Estonia, started suffering growing criticism from the media.To avoid contradictions between real behaviour and declared values the authors suggest ethics audit as solution.